Report of the Committee for Review and Strengthening of the Central and State Evaluation Organisations - Planning Commission (Planning Commission, 1980)
The importance of an efficient evaluation system in a planned economy can hardly be over emphasized. Without such a system one cannot know whether and how far the programmes and schemes, which constitute the Plan, are achieving the intended targets and the stated objectives. In fact, improvement in future policy, project formulation and administration are contingent on a proper evaluation of the field experience. Need for Evaluation: 1.02 The need for evaluation was recognised in the First Five Year Plan (1951-56) itself.
Programme Evaluation Organisation Planning Commission Government of India New Delhi